2015
DOI: 10.1590/1414-462x201500020038
|View full text |Cite
|
Sign up to set email alerts
|

Standard obesogenic diet: the impact on oral health in children and teenagers at the Recôncavo Baiano - Brazil

Abstract: The aim of this study is to evaluate the influence of dietary patterns on the occurrence of dental caries. Using a population-based, cross-sectional study design, we assessed a sample of 1.439 children aged 6-13 years who were enrolled in public schools in the municipality of São Francisco do Conde, Bahia state, Brazil. Oral examinations for dental caries were performed by two dental surgeons (Kappa = 0.72) in the school environment under natural light with the aid of a wooden spatula and gauze. Dietary intake… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 16 publications
0
8
0
5
Order By: Relevance
“…The results indicated that the evidence of an association between overweight and obesity and dental caries in Brazilian children and adolescents is contrasting and not consistent, as evaluated in other systematic reviews in which studies from several countries in the world were included. 7,16,[67][68][69] The data of the metaanalyses showed no association between obesity, overweight, overweight/obesity and dental caries for most anthropometric reference curves used to assess BMI, and had very low or low strength of evidence. Moderate strength of evidence was found for the meta-analysis showing a greater experience of dental caries in the permanent dentition of normal weight adolescents, compared with obese individuals, as classified by the CDC 2000 curve.…”
Section: Discussionmentioning
confidence: 96%
“…The results indicated that the evidence of an association between overweight and obesity and dental caries in Brazilian children and adolescents is contrasting and not consistent, as evaluated in other systematic reviews in which studies from several countries in the world were included. 7,16,[67][68][69] The data of the metaanalyses showed no association between obesity, overweight, overweight/obesity and dental caries for most anthropometric reference curves used to assess BMI, and had very low or low strength of evidence. Moderate strength of evidence was found for the meta-analysis showing a greater experience of dental caries in the permanent dentition of normal weight adolescents, compared with obese individuals, as classified by the CDC 2000 curve.…”
Section: Discussionmentioning
confidence: 96%
“…The nursing field addresses all stages of life and is present in all Brazilian cities. Nurses represent more than half of all health professionals and are essential for delivering quality health care ( 17 ) . ICPH is an important tool to meet the principle of integrality and can potentially expand access and supply, besides the qualification of health services.…”
Section: Discussionmentioning
confidence: 99%
“…(14) Evidenciou-se nos achados que 77,9% dos participantes possuíam ensino superior completo e 57,7% eram enfermeiros. Segundo a literatura, (15) os profissionais da enfermagem correspondem a mais de 50% dos profissionais de saúde no Brasil.…”
Section: Discussionunclassified